Zika: How safe is India?. Issue 1 (December 2017) - Doss, C.; Siva, R.; Christopher, B.; Chakraborty, Chiranjib; Zhu, Hailong
Abstract Zika virus, which originated from a forest in Uganda, has affected countries in Africa, Latin America and Asia. Most people infected with Zika are asymptomatic and present with clinical manifestations ranging from mild fever to severe neurological disorders. Recent outbreaks in Southeast Asian countries, Centers for Disease Control and Prevention has warned pregnant woman to avoid nonessential traveling to 11 Asian countries. Reports about the sexual transmission route of Zika have pushed the World Health Organization to declare it a 'public health emergency'. Having this current warning status, it has become mandatory to consider where second highly populated country India stands in terms of spreading awareness and taking precautionary measures against the Zika virus infection. Therefore, this paper aims to highlight the importance of Zika in Indian population by considering several indicators such as the population size and ratio, rates of mortality, closely related diseases, government initiatives, and other micro-level factors which are prone to Zika effects.